Analysis of Multiple Choice Questions on Impulse Momentum Material to See the Level of Difficulty of the Questions - Nur Ainayah; Rida Siti Nur'aini Mahmudah (Kasuari: Physics Education Journal (KPEJ), 2026)
This research aims to analyze the suitability, difficulty level, and reliability of impulse-momentum test instruments in physics subjects using the Rasch model. The background to this research is based on the importance of ensuring that the assessment instruments used in education have adequate validity and reliability. Using descriptive research methods with a quantitative approach, data were collected from 275 students from three schools in Bengkulu Province. The impulse-momentum test instrument was created and validated with the help of physics teachers from each school, and the research was conducted over 5 days. Data analysis was carried out using the QUEST application to assess the suitability of the questions under the Rasch model, the level of difficulty of the questions, and the instrument's reliability. The research results show that the majority of questions are of moderate difficulty, with instrument reliability at 0.97, indicating very good reliability. However, two items were found to have outfit values exceeding 2, indicating a mismatch with the Rasch model. In conclusion, the momentum impulse test instrument has good reliability, but several items need improvement to better align with the analytical model used. This emphasizes the importance of understanding item parameters and ensuring consistency with analytical models to ensure the validity and reliability of assessment instruments in education.